Carbon trading market policies and corporate environmental performance in China. (15th October 2022) - Yu, Xiaolin; Shi, JunWei; Wan, Kai; Chang, Tsangyao
Abstract: As an important practical exploration of energy saving and emission reduction through market mechanism, carbon emission trading market has important theoretical and practical significance on the impact of environmental performance of enterprises. This paper examines the impact of carbon market policy initiation and its improvement on corporate environmental performance. We found that: first, carbon market policy initiation can effectively improve corporate environmental performance; second, the impact of the degree of perfection of carbon market policy on corporate environmental performance has a threshold effect, and the optimal carbon market policy has a perfection interval of [0.723–0.758]; third, both internal corporate governance and corporate carbon information disclosure can form a synergistic effect with carbon market policy to promote corporate environmental performance improvement; fourth, the heterogeneity test shows that the carbon market policy has a more significant effect on the environmental performance improvement of low-cost transfer capability enterprises, high-energy-consuming enterprises and private enterprises. The findings of this paper provide new ideas to further promote the construction of governments carbon market and improve the environmental performance of enterprises. Highlights: Carbon market policies can improve corporate environmental performance. The optimal perfection interval of carbon market policies on enterprise environmental performance is [0.723–0.758]. Both internal corporate governance and carbon information disclosure can create synergies with carbon market policies. Only effective in enterprises capable of low-cost transfer, high-energy-consuming enterprises and private enterprises.